The transcriptome of circulating sexually committed Plasmodium falciparum ring stage parasites forecasts malaria transmission potential - Surendra K. Prajapati (Nature Portfolio, 2020)
Malaria gametocytes are sexual-stage parasites transmitted from mammalian host’s blood back to their insect vector. Here, Prajapati et al. identify gametocyte-committed ring-stage biomarkers allowing to forecast malaria transmission potential.